(x + 2)(5x^2 + x - 4) =
x(5x^2 + x - 4) + 2(5x^2 + x - 4) =
5x^3 + x^2 - 4x + 10x^2 + 2x - 8 =
5x^3 + 11x^2 - 2x - 8 <===
Answer:
x=1
You solve for x by cross multyplying
The term of the sequence is eleven 11
K = ln (153/147)/7
k =
<span>
ln
(<span>
<span>
1.0408163265)/7
k = </span></span></span>0.040005334584
y(t) = a * e ^ k*t
y(2017) = 147 * e^ <span><span><span>0.040005334584
</span>
</span>
</span>
* 26
y(2017) = 147*e^
<span>
<span>
<span>
1.0401386992
</span>
</span>
</span>
y(2017) = 147*
<span>
<span>
<span>
2.8296094512
</span>
</span>
</span>
<span>y(2017) = 415.95 NOT very sure of that answer
</span>